The Aeolian Environment in Glen Torridon, Gale Crater, Mars. Issue 8 (28th August 2022) - Sullivan, R.; Baker, M.; Newman, C.; Turner, M.; Schieber, J.; Weitz, C.; Hallet, B.; Ellison, D.; Minitti, M.
Abstract: The Mars Science Laboratory (MSL) rover spent a full martian year exploring the phyllosilicate‐bearing Glen Torridon trough on the flank of Aeolis Mons in Gale crater, enabling in‐depth assessment of aeolian processes. MSL encountered erosional and depositional features recording a long aeolian history. The trough has served as a long‐term conduit for sand transport, probably involving many cycles of sand accumulation and deflation. Rock abrasion textures indicate sand‐driving winds blowing W‐SW (opposite of abrasion textures on the Greenheugh Pediment above the trough floor). Indurated megaripple surfaces with 2–5 mm grains contrast with seasonally active ripples having finer maximum grain sizes, indicating more vigorous saltation in the past. Active ripples display a broad continuum of wavelengths, as well as coarser grains at crests than troughs, consistent with origins as impact ripples. Orientations of a wind streak extending from a large ripple field, and sandy wind tails behind obstacles, indicate sand is driven W‐SW in the current era, approximately along the trough axis. Erosion of drill tailings piles was strongly seasonal, enhanced during late spring and early summer (perihelion). Climate modeling suggests W‐SW sand transport can be attributed to seasonal enhancement of nighttime regional winds entering Gale crater from the N, combined with local katabatic winds flowing down the slopes of Aeolis Mons. However, it is unclear whether sand transport at Glen Torridon is primarily from these wind components combining and acting simultaneously, or occurring in serial at different times of night; field evidence supports both possibilities. Plain Language Summary: The Curiosity rover explored clay‐rich materials in the Glen Torridon trough at Gale crater for a full martian year. This enabled assessment of aeolian processes and history while simplifying comparisons between climate model predictions and observations of seasonally varying aeolian activity. Aeolian processes have contributed substantially to differential erosion excavating the Glen Torridon trough. The trough floor was lowered primarily by aeolian abrasion and transport, with coarsely surfaced megaripples developing from poorly sorted erosional debris. Large, inactive megaripples still present on the trough floor are surfaced mostly with 2–5 mm grains, coarser than grains on even the largest active dark sand ripples, indicating more vigorous sand movement in the past. Active ripples display a continuum of wavelengths, and grain size differences between crests and troughs, consistent with aeolian impact ripples. Currently, dark sand is migrating W‐SW along the trough axis during local spring and summer, as indicated by seasonally dependent erosion of drill tailings piles, observed ripple migration, and orientations of sandy wind tails behind obstacles. These observations are broadly consistent with numerical climate model results, which predict enhanced potential for aeolian activity during local spring and summer at night when regional winds from the north interact with thermally driven downslope winds. Key Points: The Curiosity rover's exploration of Glen Torridon spanned ∼1 Mars year, allowing in‐depth evaluation of aeolian processes and history A diversity of aeolian features indicates stronger saltation conditions and different sand migration directions in the past Current wind conditions evaluated from field evidence match many numerical climate model predictions, including seasonal wind activity